Inclusion/Exclusion as the Missing Link. A Luhmannian Analysis of Loneliness Among Older People. (25th October 2016) - Schirmer, Werner; Michailakis, Dimitris
Abstract : This article contributes to the interdisciplinary study of loneliness among older people with some insights based on Luhmann's systems theory. We argue that loneliness is a consequence of the way society includes/excludes people. In contrast to traditional societies, modern society forces people to act as individuals. In order to prevent loneliness, individuals themselves must search for membership in functionally diffuse collectivities (couple relations, friendships, communities). Luhmann's theory provides the framework to integrate the findings of empirical research. We claim that older people are more prone to loneliness for three reasons: first, after retirement they lose their performance role, which limits access to informal communities. Second, because they suffer from illness, impairment and a lack of resources more often than younger people, their access to functionally diffuse collectivities is impeded. Finally, because of structural and semantic changes in the family system, older people often find themselves at the margins of families. Copyright © 2016 John Wiley & Sons, Ltd.